The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/ijerph111213017
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Rates of Inpatient Mortality and Adverse Events: Race/Ethnicity and Language as Independent Contributors

Abstract: Patients with limited English proficiency have known limitations accessing health care, but differences in hospital outcomes once access is obtained are unknown. We investigate inpatient mortality rates and obstetric trauma for self-reported speakers of English, Spanish, and languages of Asia and the Pacific Islands (API) and compare quality of care by language with patterns by race/ethnicity. Data were from the United States Agency for Healthcare Research and Quality, Healthcare Cost and Utilization Project, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…However, the proportion of SMs with door-to-needle time #60 minutes did not differ between language concordant and discordant groups (8.4% [10] vs 2.5% [2], p 5 0.13, 2-tailed Fisher exact test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proportion of SMs with door-to-needle time #60 minutes did not differ between language concordant and discordant groups (8.4% [10] vs 2.5% [2], p 5 0.13, 2-tailed Fisher exact test).…”
Section: Resultsmentioning
confidence: 99%
“…1,9 Work from California using administrative claims data found lower risk-adjusted inpatient mortality for Spanish-speaking stroke patients. 10 These studies did not capture language discordance or comment on the use of interpreters. We previously showed that language discordance did not affect time to thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Language discordance can negatively impact access to healthcare services, quality of healthcare services, and patient outcomes [14,15]. Previous studies have shown that residents who live in minority language situations face barriers when accessing healthcare services [16,17], have longer emergency department visits and hospitals stays [18,19], have higher rates of hospital admissions and re-admissions [20][21][22], and experience more harmful events in hospitals [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies have considered the relationship between a patient's linguistic group and specific health-related outcomes. For instance, studies have shown that linguistic groups who live in minority language situations face barriers when accessing healthcare services [7,8], have longer emergency department visits and hospitals stays [9,10], receive lower quality discharge documentation and discharge instructions [11,12], have higher rates of hospital admissions and re-admissions [13,14], and experience more harmful events in hospitals [15][16][17][18]. However, due to limitations regarding inaccurate measurement of patients' primary language and inadequate adjustment of confounding variables, it is not known whether the differences in these studies are due to language barriers, or to systematic differences in patient characteristics (e.g., socioeconomic status) and/or health status across linguistic groups.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%